2015
DOI: 10.1186/s13014-015-0342-7
|View full text |Cite
|
Sign up to set email alerts
|

Cellular uptake and in vitro antitumor efficacy of composite liposomes for neutron capture therapy

Abstract: BackgroundNeutron capture therapy for glioblastoma has focused mainly on the use of 10B as neutron capture isotope. However, 157Gd offers several advantages over boron, such as higher cross section for thermal neutrons and the possibility to perform magnetic resonance imaging during neutron irradiation, thereby combining therapy and diagnostics. We have developed different liposomal formulations of gadolinium-DTPA (Magnevist®) for application in neutron capture therapy of glioblastoma. The formulations were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Although in the present work the endocytic mechanisms were not investigated, we speculate that the difference in the extent of internalisation between the free prodrug and the pH-sensitive liposomes could rely on the involvement of distinct uptake modalities and/or kinetics of intracellular processing. There is compelling evidence showing that liposome/nanoparticle uptake is influenced by a multitude of parameters, including nanocarrier size 52,54 , surface charge 55,56 and hydrophobicity 56,57 , lipid composition 58,59 , shape 53,56 and cell type 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…Although in the present work the endocytic mechanisms were not investigated, we speculate that the difference in the extent of internalisation between the free prodrug and the pH-sensitive liposomes could rely on the involvement of distinct uptake modalities and/or kinetics of intracellular processing. There is compelling evidence showing that liposome/nanoparticle uptake is influenced by a multitude of parameters, including nanocarrier size 52,54 , surface charge 55,56 and hydrophobicity 56,57 , lipid composition 58,59 , shape 53,56 and cell type 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…Gadolinium oxide (Gd 2 O 3 ) nanoparticles (GNPs) are extremely useful for biomedical applications because they possess various excellent physical properties applicable to cancer theragnosis . These applications include positive (T 1 ) magnetic resonance imaging (T 1 MRI), computed tomography (CT) scan, and gadolinium neutron capture therapy (GdNCT) of cancers . For biomedical applications, coating of the GNP surfaces with hydrophilic and biocompatible ligands is essential.…”
Section: Introductionmentioning
confidence: 99%
“…However, successful BNCT requires selective targeting and delivery of adequate 10 B to all tumor cells (∼ 20 μg/g weight or ∼10 9 atoms/cell). Previous studies confirmed 10 B uptake by proliferative cells targeted for killing with thermal neutrons [46]. …”
Section: Introductionmentioning
confidence: 61%